Asked by allwinligo | 22nd Sep, 2020, 07:20: PM
3x - y=23 → y = 3x - 23 ...(1)
Substitute the value of y from (1), into the equation (2), we get
4x + 3(3x - 23) = 48
→ x = 9
y = 3x - 23 = = 3(9) - 23 = 27 - 23 = 4
Therefore, the values of x and y are 9 and 4 respectively.
Answered by Yasmeen Khan | 22nd Sep, 2020, 09:44: PM
- x +2y = 1 , 3x - y = 17 by substituting method
- By Substitution
- 4/x-9/y=5 7/x-12/y=20 I did not understood how to solve this
- How to solve By substitution method.
- solve the following simultaneous linear equantion by substiution method : - 4x- 3y = 11 6x + 7y = 5
- P,Q,R have a total of ₹ 130 with them. When P gave some amount to each Q and R , their amount got doubled. P now had ₹30. Find his initial amount.
- By the substitution method solve the linear equation that is 8 x + 5 y is equal to 9 and 3 x + 2 y is equal to 4
- Two numbers are in the ratio of 3:4. If 10 is added to each numbers, the ratio becomes 5:6. Find the numbes
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number